Prevalence and risk factors of Strongyloides stercoralis infection among Orang Asli schoolchildren: new insights into the epidemiology, transmission and diagnosis of strongyloidiasis in Malaysia. Issue 12 (31st July 2019) - Al-Mekhlafi, Hesham M.; Nasr, Nabil A.; Lim, Yvonne A. L.; Elyana, Fatin Nur; Sady, Hany; Atroosh, Wahib M.; Dawaki, Salwa; Anuar, Tengku Shahrul; Noordin, Rahmah; Mahmud, Rohela
Abstract: This cross-sectional study aimed to determine the prevalence and risk factors of S. stercoralis infection among 1142 Orang Asli primary schoolchildren in six different states of Peninsular Malaysia. Fecal samples were examined using direct smear, formalin-ether sedimentation (FES), agar plate culture (APC) and PCR techniques. Overall, 15.8% of the children were found to be infected with S. stercoralis . The prevalence was 0.2, 1.3, 15.2 and 13.7% by direct smear, FES, APC and PCR, respectively. Multivariate analysis showed that an age of >10 years, being male, belonging to a Proto-Malay tribe, belonging to the Senoi tribe, indiscriminate defecation, using an unimproved water source for drinking water and not wearing shoes when outside were the significant risk factors of infection among these children. In conclusion, we provide new evidence on the occurrence of S. stercoralis in Malaysia to show that there is a relatively high prevalence of infection among Orang Asli schoolchildren. Therefore, the use of specific methods for detecting S. stercoralis should be considered when screening these children for intestinal parasites. Moreover, prevention and control measures specific to S. stercoralis should be integrated into the intestinal parasitic infections control programme in Malaysia.